Community Empowerment for Stunting Prevention: Moringa Brownies and Tempeh for Pregnant Women in South Lampung - Sefanadia Putri; Reni Indriyani; Arie Nugroho (Jurnal Abmas Negeri (JAGRI), 2026)
The high prevalence of anemia among pregnant women and the risk of stunting in Tanjungsari Village, South Lampung, motivated this Community Service (PKM) activity. This program aimed to empower the community through nutritional education and training on processing local food resources (Moringa leaves and tempeh). The implementation method employed a participatory approach, comprising education on the First 1000 Days of Life and practical demonstrations of making “Moringa and Tempeh Brownies.” Evaluation results showed significant improvements in both cognitive and psychomotor aspects. The participants' average knowledge score increased by 15.7% (from 7.78 to 9.00), with 80% of participants achieving a "very good" level of understanding. Furthermore, participants demonstrated skills in processing delicious menu variations while maintaining nutritional integrity. The program's success was marked by the commitment of Posyandu cadres to adopt this innovative product into the routine Supplementary Feeding (PMT) menu, alongside the provision of cooking equipment to ensure sustainability. Overall, this program effectively enhanced partner independence in local food-based efforts to prevent stunting and anemia.